الجرائم المتعلقة بالفاتورة وآليات ردعها في التشريع الجزائري - بن غريبي ،رضا; نسيب ،انور (جامعة الوادي University of El Oued, 2025)
بعد دراسة معمقة للأطر القانونية والتنظيمية والعملية المتعلقة بالجرائم الناشئة عن مخالفات قواعد الفواتير، أثبتنا خطورة هذه الظاهرة على الاقتصاد الوطني، لما تشكله من تهديد لشفافية المعاملات التجارية وسلامة النظام الضريبي. سعينا من خلال هذا العمل إلى تسليط الضوء على الإطار القانوني المنظم للفواتير، وتحليل أنواع الجرائم المتعلقة بها، مع إبراز مواطن القصور في النصوص القانونية والممارسات العملية. وذلك في محاولة لفهم حدود فعالية النظام القانوني الجزائري في مواجهة هذا النوع من الجرائم الاقتصادية المعقدة. After an in-depth study of the legal, regulatory, and practical frameworks related to crimes arising from breaches of the rules governing invoices, we have demonstrated the seriousness of this phenomenon to the national economy, given its threat to the transparency of commercial transactions and the integrity of the tax system. Through this work, we have sought to shed light on the legal framework governing invoices and analyze the types of crimes related to them, highlighting shortcomings in legal texts and practical practices. This is in an attempt to understand the limits of the effectiveness of the Algerian legal system in confronting this type of complex economic crime.
Keywords: فاتورة - جرائم - قانونية; invoice - crimes - legal